Corporate social responsibility, corporate governance and business ethics in tourism management : a business strategy for sustainable organizational performance - Shaikh, Erum; Singh, Kuldeep (Emerald Publishing Limited, 2024)
In recent years, there has been a rapid increase in public pressure on the accountability of business organizations. Financial crises and corporate scandals around the world have raised serious concerns about the implications for the social and environmental impacts of industry and enterprises. Consequently, there is a growing social demand for transparency in business management. These efforts to instil good practice and ethical behaviour have been particularly pronounced in the tourism and hospitality sectors, where corporate social responsibility is seen as essential for the future of the industry. Drawing on research from around the world, this collection of essays explores key challenges, solutions and applications of business ethics, CSR, and corporate governance in the tourism industry. This book will be a reading companion mainly for tourism management students in higher academic organizations but will also be of interest to professionals, policymakers, and planners in the field of tourism management and marketing.